National partnerships address critical needs in infection prevention and control - Erica Kaufman West; Michelle Doll; Margaret A. Fitzpatrick; James Lewis; Priya Nori; Catherine Passaretti; Dalilah Restrepo; Michael P. Stevens; Rama Thyagarajan; Catriona Hong (Antimicrobial Stewardship & Healthcare Epidemiology)
The COVID-19 pandemic highlighted gaps in infection control knowledge and practice across health settings nationwide. The Centers for Disease Control and Prevention, with funding through the American Rescue Plan, developed Project Firstline. Project Firstline is a national collaborative aiming to reach all aspects of the health care frontline. The American Medical Association recruited eight physicians and one medical student to join their director of infectious diseases to develop educational programs targeting knowledge gaps. They have identified 5 critical areas requiring national attention.